Цитогенетичні особливості калюсних культур тритикале озимого за дії осмотичного стресу - Пикало, С.В.; Бавол, А.В.; Дубровна, О.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. To study the effects of sublethal concentrations of mannitol on cytogenetic structure of cell populations of callus cultures of winter triticale (ЧTriticosecale Wittmack) during selection of resistant to osmotic stress forms. Methods. By cytological analysis method there were determined ploidy level, frequency of structural chromosome aberrations and mitotic abnormalities in the cells of callus cultures of winter triticale under sublethal concentrations of mannitol. Results. Analysis of genetic structure of cell populations during cultivation showed a significant increase in aneuploidy frequency and genome segregation that is shown growth of cell populations with reduced relative to the modal number of chromosomes. Conclusions. It was established that sublethal concentrations of mannitol caused significant clastogenic effect and turbagene disturbances in callus cells of triticale. Keywords: ЧTriticosecale Wittmack, callus cultures, mannitol, cytological analysis, chromosome aberrations.